2023
DOI: 10.3390/w15030381
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Trimesic Acid/Melamine Gel-Derived Fe/N-Doped Carbon Nanotubes as Catalyst of Peroxymonosulfate to Remove Sulfamethazine

Abstract: The conventional precursor preparation of metal–organic frameworks (MOFs) for nitrogen-doping carbon materials is divided into the preparation of MOFs and the mixing of the nitrogen source, which is a complex and time-consuming step. In this study, Fe-BTC gel/nitrogen source-derived carbon materials were synthesized using one or more of the following raw ingredients: Fe(NO3)3·9H2O, FeCl3·6H2O, Fe2(SO4)3, trimesic acid, melamine and dicyandiamide. The influence of different raw ingredients on the preparation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…The researchers proposed that adsorption by magnetic multi-walled carbon nanotubes (MMWCNTs) was a highly practical process due to the simplicity of design, excellent contaminant adsorption performance, and low environmental impact [24][25][26][27][28]. Previous studies have indicated that the adsorption process by MMWCNTs was capable of highly efficient removal of antibiotics [29][30][31]. Although MMWCNTs could effectively remove TC, the optimization of the adsorption effect of MMWCNTs on TC and the interaction of various factors on treatment efficiency have not been documented [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers proposed that adsorption by magnetic multi-walled carbon nanotubes (MMWCNTs) was a highly practical process due to the simplicity of design, excellent contaminant adsorption performance, and low environmental impact [24][25][26][27][28]. Previous studies have indicated that the adsorption process by MMWCNTs was capable of highly efficient removal of antibiotics [29][30][31]. Although MMWCNTs could effectively remove TC, the optimization of the adsorption effect of MMWCNTs on TC and the interaction of various factors on treatment efficiency have not been documented [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with CCD, BBD is more inclined to solve the local optimal solution (the level of BBD factors is generally less than 5) [20,49,50]. As one of the most commonly used response surface methods, the BBD avoided extreme conditions, and it had a moderate number of experiments, simple and efficient software operation, and high reliability and accuracy of optimization results, without massive training data for the simulation [25,29,[51][52][53]. The removal rate of TC in this study was affected by three factors (pH, time, and adsorbent dosage).…”
Section: Introductionmentioning
confidence: 99%
“…The Box-Behnken design (BBD) is one of the most commonly used RSM methods. It allows the modeler to explore the relationships between the design variables and the response variables without having to conduct a large number of experiments, which is the main advantage of this analysis; it also has simple and efficient software operation, and high reliability and accuracy of optimization results [30,31]. BBD has been successfully used for the optimization of process parameters in dye decolorization [32,33], heavy metal biosorption [34,35], and a wide range of other field applications [36,37].…”
Section: Introductionmentioning
confidence: 99%